Towards an international legal framework for post-conflict peacebuilding - Christian Schaller (Stiftung Wissenschaft und Politik (SWP), 2009)
The concept of post-conflict peacebuilding aims at assisting war-torn states and societies to avoid a relapse into armed conflict. To be successful in establishing the conditions for a sustainable peace, the international community may have to interfere with the domestic affairs of the affected country. Taking into account the transformative nature of peacebuilding, it is important that such action always be guided by clear normative standards. Legal certainty and predictability are fundamental cornerstones of any stable post-conflict order. Moreover, adherence to international law is a vital precondition for generating political and moral legitimacy. Therefore, international and local support for a specific peacebuilding process largely depends on whether the responsible actors are able to credibly demonstrate their respect for the rule of international law. The relevant question, however, remains as to what is the substance of the law applicable to such cases. Whilst international treaty law contains clear provisions governing the use of force in international relations and the conduct of the parties during an armed conflict no such specific rules exist for the post-conflict phase. In particular there is no international instrument offering a systematic and comprehensive catalogue of definite criteria for how to deal with war-torn states and societies in the aftermath of an armed conflict. Nevertheless, international law is by no means indifferent in this regard. It contains many general principles that may be applied to post-conflict situations. The purpose of this study is to identify some basic normative parameters for post-conflict peacebuilding and to sketch the contours of a modern "jus post bellum
Keywords: 320; Völkerrecht